Cabinets de médecine générale et notification des effets indésirables médicamenteux : expertise d’un délégué de l’Assurance maladie - Fédrizzi, Sophie; Chrétien, Basile; Sassier, Marion; Decaen, Philippe; Paul, Mehedi; Alexandre, Joachim; Humbert, Xavier (Santé Publique, 2023)
INTRODUCTION: In order to reduce the under-reporting of adverse drug reactions (ADR) in general practice, the Caen Normandie regional pharmacovigilance center (CRPV) has implemented a training program for the French health insurance representatives (DAM) of the Manche department in order to raise awareness among general practitioners (GPs) to ADR reporting. PURPOSE OF RESEARCH: During quarterly visits of DAM to GPs, the mode of operation and the value of pharmacovigilance reporting was presented. This pilot study presents the impact of these DAM visits to GPs in term of ADRs reporting quantification. RESULTS: Assessment of this first year showed a doubling of ADR reporting by GPs of the Manche department in 2019 compared to 2017 and 2018. This phenomenon was not found in the two control departments (departments of Calvados and Orne) where the information had not been issued. These ADRs first concerned drugs of the renin-angiotensin system, then psychotropic drugs and anti-infectives. These were cutaneous, then neurological and gastrointestinal ADRs, preferentially affecting women. CONCLUSIONS: This experimentation should continue on a larger scale. The longer-term evaluation of this tool also requires evaluating its relevance.